PEMANFAATAN TANAMAN PEKARANGAN DALAM UPAYA PENINGKATAN KREATIFITAS REMAJA MELALUI TEKNIK â€œOSHIBANAâ€ - Ferdinand Susilo; Jamilah Nasution; Rahmiati Rahmiati (Universitas Medan Area, 2021)
Oshibana is known as a flower processing technique so that it can produce crafts with a drying method without changing the original color of the flowers. Oshibana technique aims to produce handmade products with raw materials that come from nature, are environmentally friendly and have high selling value. Partners in this community service activity are the youth of Padepokan Igra, Kolam Village, Percut Sei Tuan District, North Sumatra. This activity aims to provide information to partners about the potential of home garden plants to be used as creative products with artistic and economic value and to introduce oshibana techniques. The implementation of the activity is carried out using 2 methods, namely the presentation of material and the delivery of information related to the potential of homegarden plants as raw material for industrial products and the direct practice of making oshibana. Through this community service activity, it is hoped that the youth at the Iqra hermitage can increase their insight and knowledge about the use of waste yard plants as raw material for creative artistic and economic products and can create jobs while supporting eco-green programs and save our earth.